Is Depressive Symptomatology Associated with Worse Oral Functioning and Well-being Among Older Adults? - Nancy R. Kressln, PhD; Avron Spiro 111, PhD; Kathryn A. Atchison, DDS, MPH; Lewis Kazis, ScD; (Blackwell Synergy, 2002)
Although depression negatively affects individuals’ physical functioning and well-being, its association with oral functioning and well-being has not been examined previously. The objective of this study was to examine the association between depressive symptomatology and oral quality of life